Employees' perspectives on one dimension of labour flexibility : working at a distance - Hamblin, Heather [Verfasser] (My University, 1995)
"This article argues that working at a distance (that is, work done in the home at a physical distance from the employer, using information-based electronic equipment for some parts of the job) will become an increasingly significant phenomenon towards the twenty-first century. This development can bring benefits to both the amployer and the individual, although other concerns regarding remote work for the individual and the organisation are discussed fully. Since the literature to date has considered working at a distance mainly from the employer's perspective, and largely in respect of professional and computing staffs, the article presents evidence from some empirical research undertaken as part of a larger study into labour flexibility: the analysis of secretarial employees' attitudes towards the flexibility of their work location and possible teleworking from home. The results, including the preferred option of working part of the week at home, are reviewed and their potential importance set within the wider labour flexibility and human resource management agendas." (author's abstract, IAB-Doku) ((en)) Die Autorin geht davon aus, dass die Telearbeit im 21. Jahrhundert stark an Bedeutung gewinnen wird, wobei sich Vorteile sowohl für die Unternehmen als auch für die Arbeitnehmer ergeben können. Während bisher in der Literatur vor allem die Sicht der Arbeitgeber betrachtet wird, erforscht der Beitrag die Einstellungen von Beschäftigten gegenüber der Arbeit aus der Distanz. Hierzu wurden im Rahmen einer grösseren Studie zur Arbeitsflexibilisierung in Grossbritannien 764 Büroangestellte (Rücklauf 30,5%) schriftlich befragt. Die meisten von ihnen glauben, dass Telearbeit ihre persönliche Freiheit erhöhen würde, sie aber mindestens genausoviele Stunden arbeiten würden wie bisher. (IAB)
Eine Dimension der Arbeitsflexibilität aus Arbeitnehmersicht : Telearbeit
Keywords: G 2.3.3 Arbeitsformen, Techniken; G 1.2.2 Beschäftigungs- und Arbeitsverhältnisse; G 2.3.2 Arbeits- & Beschäftigungsverhältnisse; G 2.3.1 Arbeitsteilung & -organisation; I 2.2.1 Westeuropa; Telearbeit; Arbeitnehmer; Einstellung; Arbeitszeitflexibilisierung; Büroarbeit; Quantitative Angaben; Großbritannien